1984
DOI: 10.1007/bf00254342
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of phase and amplitude images and left ventricle time-activity curves in assessing patients with acute myocardial infarction

Abstract: The purpose of this study was to assess the clinical usefulness of phase and amplitude images and of the left ventricle time-activity curve (LVTAC) obtained by equilibrium gated radionuclide ventriculography (EGRV) in patients with acute myocardial infarction (AMI). Fifty-six patients were studied within 4 days of the onset of AMI by EGRV; of these 49 also underwent first-pass (FP) angiocardiography, for comparison with EGRV, and 21 underwent repeated EGRV 3 months after AMI. Phase and amplitude images were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1984
1984
2008
2008

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…A similar relationship was reported earlier by Bonow et a/. (1981a,b) and Polak et al (1982) and more recently by Picozzi et al (1984). Whether or not this is a manifestation of the Starling mechanism it is impossible to ascertain at this time.…”
Section: Discussionsupporting
confidence: 85%
“…A similar relationship was reported earlier by Bonow et a/. (1981a,b) and Polak et al (1982) and more recently by Picozzi et al (1984). Whether or not this is a manifestation of the Starling mechanism it is impossible to ascertain at this time.…”
Section: Discussionsupporting
confidence: 85%
“…The left ventricular ejection fraction (LVEF) is an important clinical index for the diagnosis and selection of the treatment procedure in patients with coronary heart disease [1]. There are several modalities for the measurement of the LVEF; however, angiography is the most accurate, albeit invasive method [2,3], and echocardiography is the one most practiced [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors [17][18][19] have already reported a corre lation between right ventricular dysfunction (RVD) and the major, especially haemodynamic, complications ob served during the initial period, but an unanimous agree ment is still lacking [20][21][22], This fact prompted us to evaluate clinically and by equilibrium radionuclide angiography 100 patients with a first transmural inferior AMI with the following aims: (1) to correlate the prevalence of RVD and left ventric ular dysfunction (LVD) with that of each major in-hos pital complication and (2) to identify the major compli cations which most frequently are associated with the others.…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of regional wall motion (RWM) of the left ventricle was performed using the functional images of amplitude and phase obtained by Fourier analysis of scintigraphic data. The criteria of amplitude and phase display and interpretation can be found in the literature [20]. The segments defined on left ventricular contour were septal, inferior, and posterolateral in the left anterior oblique view and anterolateral, apical, and inferior in the anterior view.…”
mentioning
confidence: 99%
See 1 more Smart Citation